ISOLASI FUNGI ENDOFIT KULIT BUAH MERAH (Pandanus conoideus Lam.) YANG BERPOTENSI SEBAGAI ANTIBAKTERI SECARA METODE KLT - BIOAUTOGRAFI - Reza Ariyadi Deponda; Fitriana Fitriana; Siska Nuryanti; Herwin Herwin (As-Syifaa Jurnal Farmasi, 2019)
Red fruit (Pandanus conoideus Lam.) belongs to genus Pandanus. Red fruit oil has the activity as an antibacterial. The research aimed to obtain endophytic fungi isolates on the red fruit peel and assay the antibacterial activity by TLC-Bioautography. The research was experimentally conducted including the process of isolation of endophytic fungi, purification, macroscopic examination, screening for antibacterial activity against Staphylococcus aureus and Salmonella typhi, fermentation for 7, 14 and 21 days, separation and antibacterial assay by TLC-Bioautography against Staphylococcus aureus and Salmonella typhi, the isolate fermentate of endophytic fungi for 7 days showed an Rf value of 0.49 against Staphylococcus aureus and an 0.47 against Salmonella typhi. The isolate fermentate of endophytic fungi for 14 days showed an Rf value of 0.58 against Staphylococcus aureus and an 0.69 against Salmonella typhi. The isolate fermentate of endophytic fungi for 21 days showed an Rf value of 0.69 against Staphylococcus aureus and an 0.67 against Salmonella typhi. In conclusion, red fruit peel had endophytic fungi isolate with the potency as an antibacterial.